In situ δ18O and Mg/Ca analyses of diagenetic and planktic foraminiferal calcite preserved in a deep‐sea record of the Paleocene‐Eocene thermal maximum. (17th September 2013) - Kozdon, Reinhard; Kelly, D. C.; Kitajima, K.; Strickland, A.; Fournelle, J. H.; Valley, J. W.
<x xml:space="preserve">Abstract</x> [1] We report δ18O and minor element (Mg/Ca, Sr/Ca) data acquired by high‐resolution, in situ secondary ion mass spectrometry (SIMS) from planktic foraminiferal shells and 100–500 µm sized diagenetic crystallites recovered from a deep‐sea record (ODP Site 865) of the Paleocene‐Eocene thermal maximum (PETM). The δ18O of crystallites ( 1.2‰ Pee Dee Belemnite (PDB)) is 4.8‰ higher than that of planktic foraminiferal calcite (−3.6‰ PDB), while crystallite Mg/Ca and Sr/Ca ratios are slightly higher and substantially lower than in planktic foraminiferal calcite, respectively. The focused stratigraphic distribution of the crystallites signals an association with PETM conditions; hence, we attribute their formation to early diagenesis initially sourced by seafloor dissolution (burndown) ensued by reprecipitation at higher carbonate saturation. The Mg/Ca ratios of the crystallites are an order of magnitude lower than those predicted by inorganic precipitation experiments, which may reflect a degree of inheritance from "donor" phases of biogenic calcite that underwent solution in the sediment column. In addition, SIMS δ18O and electron microprobe Mg/Ca analyses that were taken within a planktic foraminiferal shell yield parallel increases along traverses that coincide with muricae blades on the chamber wall. The parallel δ18O and Mg/Ca increases indicate a diagenetic origin for the blades, but their δ18O value (−0.5‰ PDB) is lower than that of crystallites suggesting that these two phases of diagenetic carbonate formed at different times. Finally, we posit that elevated levels of early diagenesis acted in concert with sediment mixing and carbonate dissolution to attenuate the δ18O decrease signaling PETM warming in "whole‐shell" records published for Site 865.